2020
DOI: 10.1186/s13256-020-02384-y
|View full text |Cite|
|
Sign up to set email alerts
|

Elbow flexion reconstruction after arm-sparing excision for high-grade triton sarcoma: a case report

Abstract: Background: Soft tissue sarcomas affecting the root of an upper extremity raise the question of limb amputation depending on their location, size, and malignancy. Malignant triton tumors are a rare subtype of neurofibrosarcomas that have been poorly reported in the literature. We report the case of a challenging reconstruction of the upper extremity using a pedicled latissimus dorsal flap. Case presentation: A 25-year-old Occidental man was referred to our sarcoma unit for the management of a large, high-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…A bipolar pedicelled LD flap is useful when radiation or chemo-therapy was used in the recipient area [ 19 ] or if severe trauma with extensive soft-tissue defect was the main issue [ 8 ]. Furthermore, the LD flap is a reliable flap to reconstruct the upper extremity, including restoration of elbow flexion, if combined with good preoperative assessment, organized postoperative rehabilitation care, and regular follow-up [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Alexandre Gaston Lellouch.…”
mentioning
confidence: 99%